Pengembangan Media Mobile Learning untuk Meningkatkan Motivasi Belajar Siswa Sekolah Menengah Kejuruan - Pamungkas, Danu Setyo; Madyo Ekosusilo; Singgih Subiyantoro (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this study is to determine the procedure for developing Mobile Learning media in the subject of basic computers and networks for class X of SMK N Jumantono. The research method uses the (R&D) method or Research and Developments with the ADDIE model. The ADDIE model includes five components, including (A)nalysis, (D)esign, (D)evelopment, (I)mplementation, and (E)valuation. The results of the study showed that mobile learning media obtained a score of 3.50 from material experts, 3.50 from media experts and 3.50 from student respondents, so that the three validators gave a good category for mobile learning media. The effectiveness of the media was obtained from the pretest and posttest scores between classes, the results showed a significant difference. classes that liked computer and network subjects got results from 7.20 to 8.15, and classes that did not like computer and network subjects got scores from 6.75 to 7.45 with each T-test significance value of 0.01. The conclusion of the study is that mobile learning media can be used for learning activities in computer and basic network subjects in class X of SMK N Jumantono.